A Case Study of Chinese Netizens' Opinions on Capital Punishment: Diversity, Rationale, and Interaction. (November 2019) - Liu, Jianhong; Liang, Bin
Empirical studies of Chinese public opinion on capital punishment are very rare. Almost all past studies suffered from questionable survey designs and/or nonrepresentative/nonrandom sampling (e.g., student samples). In this study, to examine the breadth and the depth of public opinion on capital punishment, we turn to Chinese netizens' opinions online on a particular capital case, the Lin Senhao poisoning case. Though our netizen sample has its own limitations, it is innovative and encompasses a broader group of representations than in past studies. Specifically, we address three questions: the diversity of netizens' opinions, the rationales for netizens' support for Lin's death sentence, and netizens' interactions. This study is the first to examine Chinese netizens' opinions in a capital case in detail and to uncover potential complexities and nuances of such opinions.